2022
DOI: 10.1128/spectrum.01661-22
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Aggregates Are Localized to the Nonadherent Detached Fraction of Aging Streptococcus mutans Biofilms

Abstract: Streptococcus mutans is a keystone pathogen and causative agent of human dental caries, commonly known as tooth decay, the most prevalent infectious disease in the world. Like many pathogens, S. mutans causes disease in biofilms, which for dental decay begins with bacterial attachment to the salivary pellicle coating the tooth surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Besides P1 and WapA polypeptides, S. mutans expresses another two amyloidogenic proteins, the secreted protein Smu.63 and the serotype-restricted collagen-and lamininbinding protein Cnm, which are, respectively, required for sucrose-independent biofilm formation [23,28,41] and cardiovascular virulence [25]. Using BLASTp analysis, we confirmed that S. sanguinis genomes harbor genes encoding for P1 homologues (52% identity with S. mutans P1) but not for WapA, Smu63c or Cnm.…”
Section: Discussionmentioning
confidence: 73%
“…Besides P1 and WapA polypeptides, S. mutans expresses another two amyloidogenic proteins, the secreted protein Smu.63 and the serotype-restricted collagen-and lamininbinding protein Cnm, which are, respectively, required for sucrose-independent biofilm formation [23,28,41] and cardiovascular virulence [25]. Using BLASTp analysis, we confirmed that S. sanguinis genomes harbor genes encoding for P1 homologues (52% identity with S. mutans P1) but not for WapA, Smu63c or Cnm.…”
Section: Discussionmentioning
confidence: 73%
“…Upon mechanical stirring, both C123 and full-length P1 form insoluble aggregates that exhibit classic amyloid properties (Oli et al 2012;Besingi et al 2017;Barran-Berdon et al 2020). Recently we demonstrated that S. mutans amyloid aggregates are localized to the non-adherent fraction of aging biofilms, and that amyloid formation diminishes S. mutans adhesion (Yarmola et al 2022). Thus, the C-terminal derivative of P1 plays a major regulatory role not only in initial adhesion and biofilm genesis through quaternary interactions of its monomeric form with other P1 domains, but also in biofilm maturation and detachment through the formation of functional amyloid.…”
Section: Biological Contextmentioning
confidence: 98%
“…The conservation of a distinct β-sheet binding surface on C3 for A3VP1 and MAb interactions that is distal from the C3/C2 interface coupled with a shift for the HSE triad at this C3/C2 interface on binding suggests that protein-protein interactions lead to allosteric modulation of the internal C123 structure. Given the role of monomeric C123 binding to intact P1 on the S. mutans cell wall surface in regulating cellular adhesion and the observation that its transition from a monomeric to amyloid form correlates with biofilm detachment (Heim et al 2015;Yarmola et al 2022), we our currently pursuing NMR experiments to structurally characterize both forms of the protein and environmental triggers of dynamics or structural transitions. These CSPs provide guidance for specific residues that can be isotopically enriched for querying changes in C123 structure via lower resolution solid-state NMR measurements within the context of intact cell walls and/or functional amyloid formation (Tang et al 2016).…”
Section: Interactions Of C3 With A3vp1 and Mab 6-8cmentioning
confidence: 99%
“…Moreover, approximately 20% of S. mutans clinical isolates express the collagen- and laminin-binding adhesin Cnm (Sato et al ., 2004; Nomura et al ., 2009; Nakano et al ., 2010; Abranches et al ., 2011; Avilés-Reyes et al ., 2014b), an important virulence factor associated with dental caries severity and recurrence (Miller et al ., 2015; Esberg et al ., 2017; Garcia et al ., 2021) that also contributes to extra-oral infections such as cerebral microbleeds, hemorrhagic stroke and infective endocarditis (Abranches et al ., 2011; Nomura et al ., 2013; Miller et al ., 2015; Avilés-Reyes et al ., 2017; Inenaga et al ., 2018; Hosoki et al ., 2020; Nomura et al ., 2020; Arora et al ., 2021). In addition to binding to collagen, Cnm, WapA and P1 have also been characterized as functional amyloids that help model the biofilm structure (Oli et al ., 2012; Besingi et al ., 2017; di Cologna et al ., 2021; Yarmola et al ., 2022). In addition to sharing functional and structural similarities, Cnm and WapA were both shown to be post-translationally modified through glycosylation (Avilés-Reyes et al ., 2017; Avilés-Reyes et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%